Abnormal Cervical Cancer Screening in Pregnancy and Preterm Delivery. Issue 4 (28th May 2014) - Hong, Jennifer N.; Berggren, Erica K.; Campbell, Sara L.; Smith, Jennifer S.; Rahangdale, Lisa
Abstract Background Preterm delivery is a major cause of neonatal morbidity and mortality. Human papillomavirus (HPV) infection is common in reproductive‐aged women. We hypothesised that abnormal cervical cancer screening tests, as a proxy for HPV infection, would be associated with preterm delivery. Methods We conducted a retrospective cohort study of women delivering liveborn singletons beyond 20 weeks gestation, who had a Papanicolaou (Pap) test within 1 year prior to delivery. Women with abnormal Pap or positive high‐risk HPV tests, classified as having 'abnormal screening', were compared with women classified as having 'normal screening' in bivariate analysis for overall preterm delivery at less than 37 weeks gestation. Using Poisson regression, we report unadjusted (RR) and adjusted (aRR) risk ratios for spontaneous preterm delivery due to preterm labour and preterm premature rupture of membranes. Results Among 2686 women meeting criteria for analysis, 213 (8%) had abnormal screening. Women with abnormal screening, compared with normal screening, were not more likely to deliver preterm (12.2% vs. 9.8%, RR 1.3 [95% confidence interval (CI) 0.9, 1.8], aRR 1.2 [95% CI 0.8, 1.7]). Women with abnormal screening, however, were at greater risk for spontaneous preterm delivery in unadjusted and adjusted analysis (8.9% vs. 4.5%; RR 2.0 [95% CI 1.2, 3.2], aRR 1.8 [95% CI 1.1, 2.9]). Conclusions There was no difference in risk of overall preterm delivery in women with abnormal compared with normal cervical cancer screening tests. Our data suggest, however, that abnormal screening in pregnancy may be associated with spontaneous preterm delivery.